Recovery of Visual Function in a Patient with an Onodi Cell Mucocele Compressive Optic Neuropathy Who Had a 5-Week Interval between Onset and Surgical Intervention: A Case Report - Wencan Wu; Michelle T. Sun; Paul S. Cannon; Shi Jianbo; Dinesh Selva (Journal of Ophthalmology)
Purpose. To report on a patient with compressive optic neuropathy secondary to an Onodi cell mucocele, who fully recovered visual function following surgery. Method. Case report. Results. A 28-year-old male was admitted with a right visual acuity of 20/100 following treatment for an initial diagnosis of optic neuritis. Subsequent examination suggested compressive optic neuropathy, and neuroimaging confirmed the presence of an Onodi mucocele compressing the optic nerve. The patient underwent a right endonasal sphenoethmoidectomy with decompression 5 weeks after the initial onset of symptoms. Three weeks following surgery, the visual acuity was 20/20, and there was complete resolution of the visual field defect, which has remained stable at 1 year. Conclusion. Onodi cell mucocele should be included in the differential diagnosis of a young patient with compressive optic neuropathy. Surgical decompression should be considered even when symptoms have been present for over a month.